COMPARTEMENTALIZATION OF SANDSTONE RESERVOIR MA CA-3, MIDDLE ARANG FORMATION IN GBR FIELD, MALAY BASIN - RAHARJO (NIM: 22014032), SAFTO
GBR field is one of gas producer in the Malay Basin, Indonesia. The field has several reservoir interval zone Ma Ca-3, Ma Ca-4 and Ma Ca-5. Reservoir Ma Ca-3 are main gas producer from this field. Interference test was carried out three times in 2012 and 2015 from several wells and It is indicated that reservoir Ma Ca-3 unconnected to each other in the several wells. Therefore, reservoir modelling by doing integrated isopach map, seismic attribute and interference test need to be generated to better understanding of connectivity Ma Ca-3 reservoir among the wells. The objective of study to have distribution of Middle Arang Ca-3 reservoir both of vertically and horizontally and also to generate isopach map by integrated study of log data, depositional facies model, seismic attribute and interference test. Total nine wells log data, one core data, 3D seismic data and interference test of six wells has been used in this study. Integrated study of core description, electro facies of wireline log, seismic attribute and interference test showing reservoir Ma Ca-3 was deposited in tide dominated deltaic environtment at delta front to delta plain environtment with the reservoir geometri distributary mouth bar, distributary channel and mud marsh/flood plain. Compartementalization of reservoir Ma Ca-3 were generated by progradation process so that the distributary mouthbar was bypassed by next younger distributary channel deposition.